The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1152/jn.00569.2011
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of GABAergic and glycinergic input on FM selectivity in the inferior colliculus of the pallid bat

Abstract: Williams AJ, Fuzessery ZM. Differential roles of GABAergic and glycinergic input on FM selectivity in the inferior colliculus of the pallid bat. J Neurophysiol 106: 2523-2535. First published July 20, 2011 doi:10.1152/jn.00569.2011.-Multiple mechanisms have been shown to shape frequency-modulated (FM) selectivity within the central nucleus of the inferior colliculus (IC) in the pallid bat. In this study we focus on the mechanisms associated with sideband inhibition. The relative arrival time of inhibition com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…In these cells, for the preferred sweep direction excitation precedes inhibition, whereas for the other direction inhibition coincides with excitation. It is still debated whether this mechanism can entirely explain FM direction selectivity within the inferior colliculus, or whether there is an additional role for upstream processing or the timing of excitatory inputs (Suga, 1965; Clopton and Winfield, 1974; Poon et al, 1992; Felsheim and Ostwald, 1996; Gittelman et al, 2009; Williams and Fuzessery, 2011; Kuo and Wu, 2012). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these cells, for the preferred sweep direction excitation precedes inhibition, whereas for the other direction inhibition coincides with excitation. It is still debated whether this mechanism can entirely explain FM direction selectivity within the inferior colliculus, or whether there is an additional role for upstream processing or the timing of excitatory inputs (Suga, 1965; Clopton and Winfield, 1974; Poon et al, 1992; Felsheim and Ostwald, 1996; Gittelman et al, 2009; Williams and Fuzessery, 2011; Kuo and Wu, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Selectivity for the rate of FM sweeps can also be created by the spectrotemporal interaction of inhibitory and excitatory inputs, but additional mechanisms are thought to play a role as well (Gordon and O'Neill, 1998; Fuzessery et al, 2006; Williams and Fuzessery, 2011, 2012). Much of the rate selectivity of inferior colliculus neurons appears to be already present in their synaptic inputs (Williams and Fuzessery, 2010, 2011; Gittelman and Li, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic inhibition in the auditory system shapes spectral, temporal, and spatial selectivity properties of in vivo soundevoked responses to simple and complex sounds (Chang et al 2005;D'Angelo et al 2005;LeBeau et al 2001;Razak and Fuzessery 2009;Wang et al 2002;Williams and Fuzessery 2011). Developmental studies in the superior olivary and lateral lemniscal nuclei have shown that inhibitory synaptic properties generally become faster and more precise with age, with each auditory synapse following a unique developmental timetable (Ammer et al 2012;Awatramani et al 2005;Chirila et al 2007;Kapfer et al 2002;Magnusson et al 2005;Noh et al 2010;Walcher et al 2011).…”
mentioning
confidence: 99%
“…All data were recorded from the high-frequency region of the pallid bat IC (best frequency = 30–60 kHz) at penetration depths of 1000–2000 μm from the surface of the brain using a similar recording protocol as described previously (Razak and Fuzessery, 2009; Williams and Fuzessery, 2011). …”
Section: Methodsmentioning
confidence: 99%